Sexuality Education in Sunday Schools For Children Aged 0 –12 Years - Lucas Tjong , Andrew; Felicia Fanaya , Kezia; Binar , Sri (Jurnal Didaskalia, 2025)
Sex education for children in Sunday schools, particularly those aged 0–12 years, is a significant topic that sparks diverse opinions among church leaders. The rapid development of information technology today compels both parents and educators, within schools and churches, to provide children with sexuality education that is consistent with the teachings of God's Word. This paper, through a literature review of scholarly journals and relevant books, aims to examine the importance of sexuality education, focusing on the need to adapt it to children's developmental stages and its integration into ecclesiastical settings. Drawing from the perspective of Genesis 1:27, the goal is for children to learn to respect and honor both themselves and others, while also understanding appropriate boundaries in interpersonal relationships. Such knowledge is essential to protect children from the risk of sexual violence, which remains a critical concern.